The use of Indocyanine green fluorescent in patients with abdominal trauma for better intraoperative decision-making and less bowel anastomosis leak: case series. Issue 6 (16th June 2021) - Afifi, Ibrahim; Abdelrahman, Husham; El-Faramawy, Ahmed; Mahmood, Ismail; Khoschnau, Sherwan; Al-Naimi, Noof; El-Menyar, Ayman; Al-Thani, Hassan; Rizoli, Sandro
Abstract: Despite technological advances in the management of blunt abdominal trauma, the rate of bowel anastomotic leakage (AL) remains high. The etiology of AL is multifactorial, but insufficient blood perfusion is considered to play a substantial role in the pathogenesis. In recent years, angiography with Indocyanine green (ICG), a fluorescent dye, has been introduced in the clinical practice to assess organ perfusion in several conditions. Given the scarcity of publications describing the use of ICG in trauma patients as a potentially useful strategy that may facilitate intraoperative decisions and limit the extent of bowel resection, we presented the utility of intraoperative ICG fluorescent in abdominal trauma patients in a level 1 trauma center. The use of ICG fluoroscopy in patients with abdominal trauma is feasible and useful; however, large prospective studies in trauma patients are warranted.